ANTIOXIDANT POTENTIAL OF POLYSACCHARIDE ISOLATED FROM METHANOLIC EXTRACT OF TINOSPORA CORDIFOLIA STEM BARK - Ludas, Antony; Indu, Sabapathy; Hinduja, Sekar; Nirmala, Anthonisamy Kumari; Rajalakshmi, Manikkam (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Investigation of the antioxidant efficacy of a novel polysaccharide isolated from the methanolic extract of Tinospora cordifolia stem bark with reference to its action as free radical scavengers using in vivo and in vitro approaches was performed in the study. Methods: Lipid peroxidation (TBARS), superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) levels were determined with and without polysaccharide treatment in the cell lines and breast and liver tissues. 7, 12- Dimethylbenz (Î±) anthracene-induced albino Wistar rats were used as animal models. Results: The IC50 concentration of polysaccharide was 100 Î¼M for both the cell lines. The lipid peroxidation levels were decreased in both breast cancer cell lines and liver and breast tissues. Polysaccharide treatment showed remarkably low levels of TBARS in breast cancer cells, and a significant reduction in the activity of SOD, GPx, and CAT levels in cancer groups was found to be increased with polysaccharide treatment. The alteration was found to be induced in MCF-7 and MDA-MB-231 cell lines and in breast and liver tissues of in vivo models. Conclusion: The results showed that the polysaccharide from T. cordifolia has antioxidant potential on human breast cancer cell lines and tissues with induction of apoptosis.